KUALITAS PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI PUSKESMAS WONOAYU KABUPATEN SIDOARJO - Rosyadi, Fatkhul (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Quality of Social Service Health Service In Puskesmas In Puskesmas Wonoayu District Sidoarjo. One form of public service organized by the government is the fulfillment of public health needs through the National Health Insurance Program, the Social Security Administering Agency (BPJS) of Health. But in the service delivery, there are still problems that often occur such as, there are always long queues, inpatient rooms are often full, drugs are limited and there are usually additional costs. Puskesmas Wonoayu is one of the faskes that serves BPJS Health participants. Therefore the quality of health services is very important in serving patients BPJS Health. In general, this study aims to measure the quality of service BPJS Health Center at Wonoayu Sidoarjo. This research uses descriptive qualitative approach. The data collection method used is observation, interview, and documentation study conducted in approximately three months. The results showed that BPJS Health Service Quality at Wonoayu Public Health Center of Sidoarjo Regency measured using Lupioadi indicator which consist of direct evidence, reliability, responsiveness, assurance, and empathy is good. But in direct evidence indicator there are facilities that are still in the process of revamping and there are also equipment officers are still lacking.Keyword: Indicators of Quality of Public Service, Health Services